Improving Grade XI Students’ Writing Achievement in Analytical Exposition through Collaborative Writing Strategy - Sri Lestari Sidauruk; Tina Mariany Arifin (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2012)
This study was focused on the improvement of Grade XI students’ writing achievement in analytical exposition through the application of collaborative writing strategy. The objective of this study was to find out whether collaborative writing strategy could improve Grade XI students’ writing achievement in analytical exposition text. The study was conducted by using Classroom Action Research (CAR). The subjects of this study were students of Grade XI Class 2 of State Senior High School (Sekolah Menengah Atas Negeri: SMAN) 4 Pematangsiantar consisting of 32 students. The study was implemented in two cycles and each cycle consisted of three meetings. The instruments of data collection consisted of quantitative and qualitative data. The quantitative data were taken from students’ written test and the qualitative data were taken from the interview, diary notes, observation sheet, and questionnaire. Based on the analytical exposition writing result, students’ score was 57.9. In the test of Cycle I, the mean score was 67, and in the test of Cycle II was 78.3. Based on the observation sheet, it was found that the teaching-learning process well done. The students were active and curious in writing. In line with the data, it was found that collaborative writing strategy can improve Grade XI students’ writing achievement in analytical exposition text. Keywords: Classroom Action Research, Analytical Exposition, Collaborative Writing Strategy.